Mapping The Forms Of Hadith Mediatization Studies And Their Urgency In Indonesia - Wafa Fauziyyah; Fiqi Halwaini (TASAMUH, 2024)
Mass media significantly influences the mediatization of religious texts, such as the Qur'an and Hadith in Indonesia. The existence of Hadith mediatization can prevent the freezing of thinking. It can balance the flow of globalization so that Hadith remains alive in a space easily accessible from various circles. This paper examines the mapping of hadith mediatization studies in Indonesia and its urgency. This study maps and determines the urgency of the mediatization of hadith studies in Indonesia by analyzing the content of various mass media that discuss hadith issues. This study examines the mediatization of Hadith in Indonesia, such as print media, television, radio, internet, and social media, to disseminate, promote, or interpret the traditions of the Prophet Muhammad. The practice aims to make the traditions more accessible, understandable, and widely disseminated to a larger audience, encompassing various layers of society and culture.